1997
DOI: 10.1038/sj.bjp.0701432
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopamine and selective dopamine agonists upon platelet accumulation in the cerebral and pulmonary vasculature of the rabbit

Abstract: 1 A selection of novel compounds were shown to exhibit dopaminergic activity in vitro. 2 111 Indium-labelled platelets were continuously monitored in the cerebral and pulmonary vasculature of anaesthetized rabbits. The e ects of dopamine and selective dopamine receptor agonists on ADP and thrombin induced platelet accumulation were recorded. 3 Pretreatment with dopamine (2 mg kg 71 min 71 , i.v.) signi®cantly reduced ADP (20 mg kg 71 , i.v.) induced platelet accumulation in the pulmonary vasculature whereas lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…As mentioned above, although the existence of platelet dopamine and L-DOPA uptake system was extensively demonstrated (Boullin and O'Brien 1970;Copolov 1989a, 1989b;Dean et al 1992;Emerson et al 1997Emerson et al , 1999Martignoni et al 1999), data on the expression of dopamine receptors by platelets are conflicting (Boullin et al 1978;Khanna et al 1987;De Keyser et al 1988, 1989. Studies on the characterisation of platelet dopamine receptors were based on the use of radioligand binding assay techniques with the dopamine D1-like and D2-like receptor antagonists [ 3 H]SCH 23390 (De Keyser et al 1988, 1989 and [ 3 H]haloperidol or [ 3 H]spiperone (Boullin et al 1978;Khanna et al 1987) as radioligands.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…As mentioned above, although the existence of platelet dopamine and L-DOPA uptake system was extensively demonstrated (Boullin and O'Brien 1970;Copolov 1989a, 1989b;Dean et al 1992;Emerson et al 1997Emerson et al , 1999Martignoni et al 1999), data on the expression of dopamine receptors by platelets are conflicting (Boullin et al 1978;Khanna et al 1987;De Keyser et al 1988, 1989. Studies on the characterisation of platelet dopamine receptors were based on the use of radioligand binding assay techniques with the dopamine D1-like and D2-like receptor antagonists [ 3 H]SCH 23390 (De Keyser et al 1988, 1989 and [ 3 H]haloperidol or [ 3 H]spiperone (Boullin et al 1978;Khanna et al 1987) as radioligands.…”
Section: Discussionmentioning
confidence: 96%
“…In vivo investigations reported that dopamine and dopamine receptor agonists can modify platelet function (Emerson et al 1997(Emerson et al , 1999. However, since the first reports of the presence of dopamine receptors in platelets De Keyser et al 1988), subsequent studies did not provide conclusive results (Boullin et al 1978;De Keyser et al 1989;Anfossi et al 1992Anfossi et al , 1993Dean et al 1992).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In lieu of dopamine's integral part in positive reinforcement, these data suggest that alcohol intake is reinforced by the feel-good sensations as a result of DA's stimulated/increased release [20]. According to Emerson et al [21], pretreatment with dopamine alone in concentrations of 2 mg/kg/min (higher than therapeutic levels) increased platelet accumulation in the lungs in response to thrombin and induced thrombocytopenia. Blood levels of dopamine are also increased in patients with renal insufficiency [22].…”
Section: Discussionmentioning
confidence: 92%